2016
DOI: 10.3390/ijms17081283
|View full text |Cite
|
Sign up to set email alerts
|

Zeb1 Is a Potential Regulator of Six2 in the Proliferation, Apoptosis and Migration of Metanephric Mesenchyme Cells

Abstract: Nephron progenitor cells surround around the ureteric bud tips (UB) and inductively interact with the UB to originate nephrons, the basic units of renal function. This process is determined by the internal balance between self-renewal and consumption of the nephron progenitor cells, which is depending on the complicated regulation networks. It has been reported that Zeb1 regulates the proliferation of mesenchymal cells in mouse embryos. However, the role of Zeb1 in nephrons generation is not clear, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…A phenotypic clinical feature of FECD is the development of corneal guttae, which are abnormal collagenous excrescences of the corneal endothelial basement membrane (Descemet’s membrane). Recent studies have shown that Snail and ZEB1 can also reduce cell adhesion, increase cell migratory capacity [7476], and promote apoptosis [77, 78]. These phenotypic features have also been observed during FECD pathogenesis [7981].…”
Section: Discussionmentioning
confidence: 99%
“…A phenotypic clinical feature of FECD is the development of corneal guttae, which are abnormal collagenous excrescences of the corneal endothelial basement membrane (Descemet’s membrane). Recent studies have shown that Snail and ZEB1 can also reduce cell adhesion, increase cell migratory capacity [7476], and promote apoptosis [77, 78]. These phenotypic features have also been observed during FECD pathogenesis [7981].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a process that is prominent in embryonic development, but its aberrant induction is linked to invasiveness of epithelial cancer cells via promoting their migration, invasion, and dissemination (Zhang et al 2015). ZEB-1 increases EMT by suppression of CDH1 (encoding E cadherin, an epithelial marker) and microRNA 200 (Gu et al 2016). This leads to the activation of the TGF-β1 signaling pathway and elicits unregulated proliferation of cancer cells and their invasion (Gu et al 2016).…”
Section: Other Major Migratory Pathways That Could Be Potentially Expmentioning
confidence: 99%
“…ZEB-1 increases EMT by suppression of CDH1 (encoding E cadherin, an epithelial marker) and microRNA 200 (Gu et al 2016). This leads to the activation of the TGF-β1 signaling pathway and elicits unregulated proliferation of cancer cells and their invasion (Gu et al 2016). In addition, ZEB-1 has been implicated in animal organ development, cartilage development, and regulation of MSC proliferation, as well as the establishment of a motile and drug-resistance tumor phenotype (Gu et al 2016).…”
Section: Other Major Migratory Pathways That Could Be Potentially Expmentioning
confidence: 99%
See 1 more Smart Citation
“…When the signaling for the process of induction is successful, a few mesenchymal cells separate, aggregate, and perform a mesenchyme-to-epithelial transition (MET) to develop into a renal vesicle at the lateral aspect of the related CD ampulla [63]. For remaining and not induced mesenchymal cells, the transcription factor Zeb1 controls the balance between further proliferation, migration, and apoptosis [64]. Thus, repeated branching of a CD tubule, approximation of a CD ampulla tip to competent mesenchymal cells, and finally timely induction superimposes new nephrons beyond the capsule [42].…”
Section: Fine Positioning Of Stem Cellsmentioning
confidence: 99%